2006
DOI: 10.1183/09031936.06.00019106
|View full text |Cite
|
Sign up to set email alerts
|

Is it time to rethink the urea criterion in CURB-65?

Abstract: We read the article by CAPELASTEGUI et al.[1] on the validation of the severity assessment rules for the management of community-acquired pneumonia (CAP) with interest. The authors concluded that CURB-65 (confusion, urea .7 mmol? L -1 , respiratory rate o30?min -1 , low systolic (,90 mmHg) or diastolic (f60 mmHg) blood pressure, and aged o65 yrs) and CRB-65 indices recommended by the British Thoracic Society are indeed useful and easy to apply in day-to-day clinical practice, thereby helping in risk stratifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…When classifying patients into high‐ and low‐risk groups, the new tool had the advantage of including a smaller proportion of the total number of patients presenting to the ED than CRB65 (41.4% vs 63.6%). This percentage differed from previous studies of CRB65, because our study did not include the many patients who might be managed by a general practitioner, 15 but instead focused only on patients referred to the hospital. Importantly, this does not imply that all 41.1% would be admitted to ICU, but instead that inexperienced doctors would seek assistance when assessing this patient group, and would evaluate these patients more closely.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…When classifying patients into high‐ and low‐risk groups, the new tool had the advantage of including a smaller proportion of the total number of patients presenting to the ED than CRB65 (41.4% vs 63.6%). This percentage differed from previous studies of CRB65, because our study did not include the many patients who might be managed by a general practitioner, 15 but instead focused only on patients referred to the hospital. Importantly, this does not imply that all 41.1% would be admitted to ICU, but instead that inexperienced doctors would seek assistance when assessing this patient group, and would evaluate these patients more closely.…”
Section: Discussionmentioning
confidence: 91%
“…one additional variable). Accuracy must be balanced against simplicity and practicality for use at the point of care 15–18 . Hypoxia is, however, usually easy to measure by pulse oximetry; hence, its inclusion in a tool is probably justified.…”
Section: Discussionmentioning
confidence: 99%
“…Currently recommended severity assessment criteria by BTS were based on the CURB-65 developed by Lim et al (6). However, their usefulness in the elderly patients with CAP has been questioned (7,8). We have shown that simple modification of CURB-65 using CURB-age criteria better identified patients who are at high risk of mortality from CAP (9).…”
Section: Introductionmentioning
confidence: 99%